Clinical management of severe infections caused by carbapenem-resistant gram-negative bacteria: a worldwide cross-sectional survey addressing the use of antibiotic combinations. (January 2022) - Carrara, Elena; Savoldi, Alessia; Piddock, Laura J.V.; Franceschi, Francois; Ellis, Sally; Sharland, Mike; Brink, Adrian John; Harris, Patrick N.A.; Levy-Hara, Gabriel; Rohit, Anusha; Tsioutis, Constantinos; Zayyad, Hiba; et al.
Abstract: Objectives: Optimal treatment of carbapenem-resistant Gram-negative bacteria (CR-GNB) infections is uncertain because of the lack of good-quality evidence and the limited effectiveness of available antibiotics. The aim of this survey was to investigate clinicians' prescribing strategies for treating CR-GNB infections worldwide. Methods: A 36-item questionnaire was developed addressing the following aspects of antibiotic prescribing: respondent's background, diagnostic and therapeutic availability, preferred antibiotic strategies and rationale for selecting combination therapy. Prescribers were recruited following the snowball sampling approach, and a post-stratification correction with inverse proportional weights was used to adjust the sample's representativeness. Results: A total of 1012 respondents from 95 countries participated in the survey. Overall, 298 (30%) of the respondents had local guidelines for treating CR-GNB at their facility and 702 (71%) had access to Infectious Diseases consultation, with significant discrepancies according to country economic status: 85% (390/502) in high-income countries versus 59% (194/283) in upper-medium-income countries and 30% (118/196) in lower-middle-income countries/lower-income-countries). Targeted regimens varied widely, ranging from 40 regimens for CR- Acinetobacter spp. to more than 100 regimens for CR- Enterobacteriaceae . Although the majority of respondents acknowledged the lack of evidence behind this choice, dual combination was the preferred treatment scheme and carbapenem-polymyxin was the most prescribed regimen, irrespective of pathogen and infection source. Respondents noticeably disagreed around the meaning of 'combination therapy' with 20% (150/783) indicating the simple addition of multiple compounds, 42% (321/783) requiring the presence of in vitro activity and 38% (290/783) requiring in vitro synergism. Conclusions: Management of CR-GNB infections is far from being standardized. Strategic public health focused randomized controlled trials are urgently required to inform evidence-based treatment guidelines.